RESPONSE OF ZINC SULPHATE ON GROWTH, YIELD AND QUALITY OF POTATO - Joshi, Neelima; Raghav, Manoj (Potato Journal, 2013)
A field experiment was conducted with potato cultivar Kufri Jawahar during winter seasons of 2002-03 and 2003-04 at Pantnagar. The potato tuber yield increased significantly by the application of zinc sulphate. Recommended doses (RDF) of NPK + foliar application of ZnSO4 @ 0.5% at 35, 45 and 55 days after planting gave yield followed by RDF+ ZnSO4 @ 1.0% (foliar) and RDF+ ZnSO4 @ 20Kg/ha as soil application. Foliar application of zinc sulphate was found superior as compared to tuber soaking and soil application.